Highly selective ionic liquid-based microextraction method for sensitive trace cobalt determination in environmental and biological samples - Berton, Paula (2010)
A simple and rapid dispersive liquid?liquid microextraction procedure based on an ionic liquid (ILDLLME) was developed for selective determination of cobalt (Co) with electrothermal atomic absorption spectrometry (ETAAS) detection. Cobalt was initially complexed with 1-nitroso-2-naphtol (1N2N) reagent at pH 4.0. The IL-DLLME procedure was then performed by using a few microliters of the room temperature ionic liquid (RTIL) 1-hexyl-3-methylimidazolium hexafluorophosphate [C6mim][PF6] as extractant while methanol was the dispersant solvent. After microextraction procedure, the Co-enriched RTIL phase was solubilized in methanol and directly injected into the graphite furnace. The effect of several variables on Co-1N2N complex formation, extraction with the dispersed RTIL phase, and analyte detection with ETAAS, was carefully studied in this work. An enrichment factor of 120 was obtained with only 6 mL of sample solution and under optimal experimental conditions. The resultant limit of detection (LOD) was 3.8 ng/L, while the relative standard deviation (RSD) was 3.4% (at 1 ug/L Co level and n = 10), calculated from the peak height of absorbance signals. The accuracy of the proposed methodology was tested by analysis of a certified reference material. The method was successfully applied for the determination of Co in environmental and biological samples.